2016
DOI: 10.1111/ppe.12285
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low Maternal Education on Early Childhood Overweight and Obesity in Europe

Abstract: Considerable inequalities in overweight and obesity are evident among European children in early life. Tackling early childhood adiposity is necessary to promote children's immediate health and well-being and throughout the life course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 29 publications
(39 reference statements)
8
69
2
4
Order By: Relevance
“…As shown in Table , we identified 12 unique meta‐analyses of observational studies investigating associations of risk factors for obesity in children and adolescents, which were derived from 11 unique references, plus one that failed to show any nominally significant (ie P < 0.05) associations of weight gain during pregnancy and obesity during both childhood and adulthood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table , we identified 12 unique meta‐analyses of observational studies investigating associations of risk factors for obesity in children and adolescents, which were derived from 11 unique references, plus one that failed to show any nominally significant (ie P < 0.05) associations of weight gain during pregnancy and obesity during both childhood and adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…Details of grading of evidence of meta-analyses that assessed environmental risk factors for obesity in children from cohort studies are provided in Table 2. Three risk factors for childhood obesity, namely infancy weight gain during the first year of life, 56 depression 59 and low maternal education 64 were supported by convincing (type I) evidence, while no risk factors were supported by type highly suggestive (type II) evidence. The meta-analytic reviews that provided study-level data for the associations of depression 59 and low maternal education 64 had high methodological quality scores based on the AMSTAR tool, while the meta-analysis that provided data for the association of weight gain during the first year of life and paediatric obesity 56 had low methodological quality score (Table S6).…”
Section: Grading Of Evidencementioning
confidence: 95%
“…Parental education has also been reported to be inversely related to child excess weight and studies have shown a higher prevalence of overweight and/or obesity in children of parents with a low educational level (24,25,26). Previous studies across 11 European countries have indicated that low maternal education could yield a substantial risk of early childhood obesity (27). In another study, it was reported that children of better educated mothers had a more favorable growth pattern, namely, lower overweight and obesity rates (in the UK and Sweden), and lower stunting and underweight rates (in rural China) (28).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was reported that children of better educated mothers had a more favorable growth pattern, namely, lower overweight and obesity rates (in the UK and Sweden), and lower stunting and underweight rates (in rural China) (28). It seems that maternal education has a more substantial effect on child weight status, because mothers spent a longer time with their children than the fathers and are usually the person who prepares the food (27). Also, there is a more direct interaction between the children and their mothers than their fathers (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature undeniably shows the prevalence of overweight and obesity in children, most studies rely on mothers' self-report, and lacked measurement of combined factors. The few studies that did measure combined factors inconsistent findings [27][28][29].…”
Section: Resultsmentioning
confidence: 99%